Integrating Applied Learning and Community Outreach into Online Education - Katherine Adler; Mary-Katherine Smith (Academic Chairpersons Conference Proceedings, 2018)
For online schools and programs fulfilling service requirements can be challenging. To address this issue, an online program can utilize an integrated outreach program with local stakeholders. This session explores how to link applied learning and community outreach to allow students to impact the local community while experiencing applied learning and increasing the presence of the online program in communities.
Keywords: Competencies in Education; Competency Mapping